Potential health benefits of aloe vera - Natalia Mikołajczak (Kazimierz Wielki University, 2018)
Introduction and aim: Aloe vera was known in antiquity, and then its versatile healing and cosmetic properties were used. It is a rich source of many chemical compounds; it has been shown that there are 75 biologically active compounds, i.e. vitamins, minerals, enzymes, sugars, phenolic compounds, sterols, amino acids. The aim of this article was to review the literature and gather information on the health benefits of aloe vera and its products. Brief description of the state of knowledge: There are many studies in the available literature on the influence of aloe vera and its products on human health. Studies carried out with the use of an aloe gel extract have shown that methanol and acetone solutions have maximum radical scavenging abilities. Other sources report that the use of aloe vera had a beneficial effect on the treatment of first and second degree burns, in addition the use of aloe vera gel in 63 male wounded rats increased the healing power of wounds than in other groups. Aloe vera juice is useful in the treatment of gastrointestinal problems, such as indigestion, yeast, heartburn and irritable bowel syndrome. Aloe vera extract increased cell tolerance to glucose in healthy and diabetic rats, and the use of aloe vera juice (4 - 14 weeks) had a significant hypoglycemic effect. Summary: The collected literature data show that aloe vera, as well as its products have a beneficial influence of human health. They exhibit properties such antioxidant, anti-inflammatory, anti-cancer, antimicrobial, immunomodulatory, lipid and blood sugar lowering properties, and also accelerate the healing of wounds and burns. Aloe vera also has a beneficial effect on people's appearance (skin, hair, nails), thanks to which it finds a wide use in the cosmetics industry. Despite so many benefits, people should pay attention to the side effects of using aloe vera. It is also important to continue research (both with animals and people) related to the influence of this plant and its products on health.